Established a therapeutic response prediction model in metastatic gastric cancer by liquid biopsy - Sheng Liu; Huacong Zhu; Shi‐Tong Yu; Jiaolong Shi (Wiley, 2024)
Abstract This study by Okuno et al. successfully identified eight exo‐miRNAs through exosome‐based discovery and established an exo‐miRNA‐based liquid biopsy assay for predicting therapeutic response in metastatic gastric cancer (mGC). Exosomes, a subpopulation of extracellular vesicles originating from endosomes, play a crucial role in this context. Liquid biopsy, analyzing blood for circulating tumor cells, extracellular vesicles, or cell‐free nucleic acid, has revolutionized cancer diagnosis and monitoring. It significantly contributes to early detection, staging, and relapse detection in various cancers. Numerous studies have highlighted the clinical significance of miRNA and lncRNA within extracellular vesicles. The authors developed a response‐prediction model for chemo‐responsiveness in mGC patients. This study's model predicts responses robustly, demonstrating its potential efficacy in clinical practice. It offers a non‐invasive and accessible method for therapeutic response prediction, crucial for precision medicine in mGC. Successful translation of these findings into clinical applications promises substantial benefits for patient care.